DIAGNOSIS AND MANAGEMENT OF ANOREXIA NERVOSA - Collin Peters; Nyoman Ratep; Wayan Westa (Bali Journal of Medical and Health Sciences, 2013)
Anorexia nervosa (AN) is a type of eating disorder, but it is more importantly a serious psychiatric illness associated with significant medical and psychiatric morbidity, psychosocial impairment and increased risk of death. The clinical features are characterized by deliberate weight loss, arising from food avoidance often in combination with self-induced vomiting, excessive exercise and using diuretics and appetite suppressants. Diagnostic and Statistical Manual of Mental Disorders (DSM-IV) criteria is used to determine if the patient is suffering from anorexia nervosa. Anorexia can have dangerous psychological and behavioral effects if left untreated. The treatment of anorexia has to focus on more than weight gain and the physical damage caused by malnutrition. It must also focus on the psychological cause. Keyword: Anorexia nervosa, eating disorders, psychotherapy